Kesesuaian Fatwa DSN-MUI No 106 Dengan Praktik Wakaf Polis Di Lembaga Wakaf Al-Azhar Jakarta - Hendra Kholid; Maulida Rahmawati (Fakultas Syariah dan Ekonomi Islam Institut Ilmu Al-Qur'an (IIQ) Jakarta, 2020)
This study aims to analyze the mechanism of waqf policy in the Al-Azhar Waqf Institute so that the community response is so good and an increase in the number of participants in the waqf policy so rapidly that it reaches 200 policies. And how is the compatibility of the mechanism with the National Sharia Board Fatwa No. 066 / DSN-MUI / IXl2016 About Waqf Insurance Benefits and Investment Benefits in Sharia Life Insurance (waqf policy). The mechanism of implementing a policy waqf carried out by the Al-Azhar Waqf Institute has general and specific provisions namely; General provisions, namely waqf must be puberty, have full rights to the assets to be represented, follow the provisions of the Islamic insurance company, make a waqf pledge witnessed by witnesses, and pledge waqf legalized by a notary; Specific provisions namely endowments are given the discretion to choose waqf objects including for the construction of mosques, construction of Islamic boarding schools, productive endowments, Islamic institutions, social charity institutions, business entities owned by Al-Azhar Waqf, or endowment objects can be given to other institutions with entities law. The results showed that the mechanism of implementing waqf policies in Al-Azhar Waqf Institutions was considered to be in accordance with DSN-MUI fatwa No.106 / DSN-MUI / IX2016 regarding endowments of insurance benefits and investment benefits in sharia life insurance..